A new species of Bituminaria (Fabaceae) from Tunisia - Brullo, Cristian; Brullo, Salvatore; Cambria, Salvatore; Mokni, Ridha El; Aouni, Mohamed Hédi El; Galdo, Gianpietro Giusso Del (Phytotaxa, 2017)
Bituminaria tunetana a new species occurring in Tunisia is described and illustrated. It shows some relationships with B. basaltica from Aeolian Archipelago (Sicily), mainly for having very small flowers and also with B. flaccida from Middle East in having pale colored corolla and few-flowered inflorescences, but the three species differ among them in many diacritic features regarding the leaves, flowers, fruits and seeds. Besides, it is well distinct from B. bituminosa, species widely spread in Sicily and in several countries of the Mediterranean area, for many morphological features, as well as in micro-morphology of seed testa and pod indumentum. Its distribution, ecology and conservation status are also examined. An analytical key of the species belonging to Bituminaria subgen. Bituminaria is also provided.